2022
DOI: 10.1111/ele.13959
|View full text |Cite
|
Sign up to set email alerts
|

No complementarity no gain—Net diversity effects on tree productivity occur once complementarity emerges during early stand development

Abstract: Although there is compelling evidence that tree diversity has an overall positive effect on forest productivity, there are important divergences among studies on the nature and strength of these diversity effects and their timing during forest stand development. To clarify conflicting results related to stand developmental stage, we explored how diversity effects on productivity change through time in a diversity experiment spanning 11 years. We show that the strength of diversity effects on productivity progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 53 publications
6
35
0
Order By: Relevance
“…This is in line with previous findings showing that selection effects play a major role at the beginning, but are replaced by complementarity effects after some time (Fargione et al, 2007;Jing et al, 2021;Lasky et al, 2014). Overall, our results support the hypothesis that co-occurring species in high-diverse temperate forests differ in niches and competitive abilities, which leads to strong biodiversity effects and higher productivity in mixtures compared to their monospecific counterparts Huang et al, 2018;Morin et al, 2011;Urgoiti et al, 2022). Our results extend this knowledge by showing that both complementarity and selection effects contribute to biodiversity effects on tree growth in young tree stands.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with previous findings showing that selection effects play a major role at the beginning, but are replaced by complementarity effects after some time (Fargione et al, 2007;Jing et al, 2021;Lasky et al, 2014). Overall, our results support the hypothesis that co-occurring species in high-diverse temperate forests differ in niches and competitive abilities, which leads to strong biodiversity effects and higher productivity in mixtures compared to their monospecific counterparts Huang et al, 2018;Morin et al, 2011;Urgoiti et al, 2022). Our results extend this knowledge by showing that both complementarity and selection effects contribute to biodiversity effects on tree growth in young tree stands.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have shown a positive biodiversity-ecosystem functioning (BEF) relationship in terrestrial ecosystems, and that this relationship strengthens over time (Bongers et al, 2021; Cardinale et al, 2007; Fargione et al, 2007; Guerrero-Ramirez et al, 2017; Huang et al, 2018; Reich et al, 2012; Urgoiti et al, 2022). Typically, this relationship is explained by complementary resource use among plants, as well as a growing intensity of negative plant-soil interactions at low diversity and positive interactions at high diversity (Barry et al, 2019; Eisenhauer 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with previous findings showing that SEs play a major role at the beginning but are replaced by CEs after some time (Fargione et al, 2007;Jing et al, 2021;Lasky et al, 2014). Overall, our results support the hypothesis that co-occurring species in high-diversity temperate forests differ in niches and competitive abilities, which leads to strong biodiversity effects and higher productivity in mixtures compared to their monospecific counterparts (Bongers et al, 2021;Huang et al, 2018;Morin et al, 2011;Urgoiti et al, 2022). Our results extend this knowledge by showing that both CEs and SEs contribute to biodiversity effects on tree growth in young tree stands.…”
Section: Discussion Hypothesis 1 Diversity-productivity Relationships...supporting
confidence: 93%
“…Numerous studies have shown a positive biodiversity–ecosystem functioning (BEF) relationship in terrestrial ecosystems and that this relationship strengthens over time (Bongers et al, 2021; Cardinale et al, 2007; Fargione et al, 2007; Guerrero‐Ramirez et al, 2017; Huang et al, 2018; Reich et al, 2012; Urgoiti et al, 2022). Typically, this relationship is explained by complementary resource use among plants and a growing intensity of plant–soil interactions over time—at low plant diversity an accumulation of pathogens leads to a loss of productivity over time, whereas a high plant diversity can host different soil mutualists complementing each other and, thereby, increasing plant productivity (Barry et al, 2019; Eisenhauer, 2012; Eisenhauer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This means that one limitation of our current study is the documented changes in vegetation composition have not been compared directly with native woodlands in which these tree and shrub species naturally occur. Therefore, our discussion of ways in future to prevent the biodiversity decline of plantings is based on the broader ecological and social value of biodiversity (Chapin III et al 2000;Urgoiti et al 2022) and is not driven by a benchmark from a climax vegetation community.…”
Section: Discussionmentioning
confidence: 99%